2022
DOI: 10.1016/j.inteco.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of a suspicion of tax fraud indicator based on Google trends to foresee Spanish tax revenues

Abstract: This article contributes to the relationship between fiscal fraud and tax collection in the Spanish economy, creating a composite suspicion tax fraud indicator (STFI) based on Google Trends searches to study the dynamics and foresee tax revenues evolution in Spain. Also, we expand knowledge in the field of fraud tax indicators, following the UNODC (2020) and OECD (2016) recommendations. To this purpose, we apply factor analysis to create the composite indicator and next we utilize techniques centred on fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…To handle [12] large-scale non-uniform transactions more quickly, the authors employ the AR model, which makes it appropriate for detecting money laundering operations. The study [11] uses factor analysis to generate the composite indicator, fractional integration (ARFIMA), and fractional cointegration VAR (FCVAR) approaches to evaluate the behavior of the composite suspicion tax fraud indicator about GDP and tax collection. The study [13] employs the AR model, which is appropriate for studying networks with such topologies and applying it to the detection of financial transaction fraud since it considers the block-wise structure of networks.…”
Section: A Statistical Methods Of Fraud Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To handle [12] large-scale non-uniform transactions more quickly, the authors employ the AR model, which makes it appropriate for detecting money laundering operations. The study [11] uses factor analysis to generate the composite indicator, fractional integration (ARFIMA), and fractional cointegration VAR (FCVAR) approaches to evaluate the behavior of the composite suspicion tax fraud indicator about GDP and tax collection. The study [13] employs the AR model, which is appropriate for studying networks with such topologies and applying it to the detection of financial transaction fraud since it considers the block-wise structure of networks.…”
Section: A Statistical Methods Of Fraud Detectionmentioning
confidence: 99%
“…Even tree is employed in risk assessment and analysis to pinpoint different event sequences for both fraud and nonfraud that may result in a particular outcome. An event tree also known as an incidence response tree (IRT) [49] contains four possible outcomes as given (9)(10)(11)(12) that are based on prevention, detection, and response. The event tree significantly tracks fraudulent activities and estimates the return outcomes of monitoring decisions, hence improving prediction and risk models.…”
Section: ) Tree Event Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Their study demonstrates a positive correlation between forensic accounting skills and the detection of tax evasion, indicating that enhancing these skills can lead to more effective tax fraud detection. Monge, Poza and Borgia (2022) propose a big data analytics-based approach to tax evasion detection. By applying algorithms like K-means clustering and decision trees, their system can characterize and detect probable tax evaders, showcasing the potential of big data analytics in enhancing tax fraud detection.…”
Section: Impact On Tax Fraud Detection and Preventionmentioning
confidence: 99%
“…Finally, the research carried out by [56][57][58][59] suggests that misleading results will be found if we apply a typical cross-correlation to study statistical relationships between two multifractal time series.…”
Section: Wavelet Analysismentioning
confidence: 99%